2008
DOI: 10.4038/cjms.v49i1.124
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of selection criteria as a measure of outcome of medical graduates: University of Colombo

Abstract: A prime obstacle faced by a medical educator is selecting the right student to be trained as a doctor, and the general consensus is that . this is a Iso the most difficult task. This stud y was designed to evaluate the effects of selected outcome measures on outcome performance of medical undergraduates of the University of Colombo.A retrospective cohort stud y was cond ucted using the performance (marks) of students of 4 batches GCE (AIL) 1993 through to 1996). GCE (AIL) aggregate marks, attempt of entry, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In addition entering university in the 1 st attempt also increased the odds of obtaining a ‘Honours’ degree at the final MBBS examination. Similar findings have been demonstrated by two different authors from Sri Lanka [7,8]. Therefore serious consideration must be given about revising the admission criteria to medical schools and restricting the number of attempts by a student at GCE A/L examination to gain university admission.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition entering university in the 1 st attempt also increased the odds of obtaining a ‘Honours’ degree at the final MBBS examination. Similar findings have been demonstrated by two different authors from Sri Lanka [7,8]. Therefore serious consideration must be given about revising the admission criteria to medical schools and restricting the number of attempts by a student at GCE A/L examination to gain university admission.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, to be eligible for selection under this criterion, a student must obtain at least a ‘Simple’ pass for each of the three GCE A/L subjects. Recent studies have demonstrated that this sole admission criterion is a poor predictor of academic success of Sri Lankan medical students [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Sri Lankan medical schools have suggested that the A/L aggregate score is a weak predictor of success in medical school [2], and that other variables such as the attempt at the GCE A/L examination and proficiency in English may also be used as predictors of outcome in medical school examinations [3,4]. Since these studies were carried out, the curricula for the GCE A/L examination has changed, and the means of ranking students for selection to university has also changed, from aggregate marks to z-scores.…”
Section: Introductionmentioning
confidence: 99%
“…A/L examination, their attempt of entry, the district of entry, English language proficiency (as judged by the G.C.E. O/L results), and sex as predictor variables (Mettananda et al, 2006). The outcome was based on results at six major assessments in medical school, the cumulative MBBS exam mark and the graduate's position in merit order for internship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A/L) examination in Sinhala or Tamil and apply for admission to study Medicine are not required to show any evidence of proficiency in English. Several studies conducted in Sri Lanka have shown that students with better skills in English at the time of admission perform significantly better in medical school (Mendis & Babapulle 1983, De Silva et al, 2004De Silva et al, 2006a;Mettananda et al, 2006;De Silva et al, 2006b;Hewage et al, 2011). This is despite the fact that almost all medical faculties conduct a three-month intensive course in English on registration of their medical students.…”
Section: Introductionmentioning
confidence: 99%